Fair Traffic Scheduling and Shaping Algorithms for Diffserv Networks - Mohamed, Mohamed Awad Elshaikh (2006)
Traditionally, the Internet has provided only best effort service to every user without any consideration to any requirements. As the Internet grows and becomes universally available, it becomes very important to deal with real time service delivery to application such as IP telephony. Thus, an interest has developed in having the Internet to provide some degree of Quality of Service (QoS). To provide different QoS commitments, the IETF developed many technologies that requires resources such as bandwidth and buffers to be explicitly reserved for a given data flow to ensure that the application receives its requested QoS.